Il cancro di origine professionale: una piaga sociale troppo spesso ignorata - Mengeot, Marie-Anne (Roma, 2007)
"There were more than a million deaths from cancer in the European Union in 2006. A significant percentage of these deaths were caused by workers being exposed to carcinogens at the workplace. These include asbestos, of course, but also an endless number of toxic petrochemical substances or dust that can prove deadly after years of exposure, for example, hard wood dust.